Respuesta :

Answer:

(x - 1)(2x + 1)

Step-by-step explanation:

Given

2x² - x - 1

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 2 × - 1 = - 2 and sum = - 1

The factors are - 2 and + 1

Use these factors to split the x- term

2x² - 2x + x - 1 ( factor the first/second and third/fourth terms )

2x(x - 1) + 1 (x - 1) ← factor out (x - 1) from each term

= (x - 1)(2x + 1) ← in factored form

ACCESS MORE